Designed cellulose nanocrystal surface properties for improving barrier properties in polylactide nanocomposites. (1st March 2018) - Espino-Pérez, Etzael; Bras, Julien; Almeida, Giana; Plessis, Cédric; Belgacem, Naceur; Perré, Patrick; Domenek, Sandra
Graphical abstract: Highlights: Surface grafting of cellulose nanocrystals reduces nanocomposite water swelling. Permeant trapping at cellulose nanocrystal surface decreases non-Fickian transport rate. Cellulose nanocrystals add little tortuosity in PLA nanocomposites. Abstract: Nanocomposites are an opportunity to increase the performance of polymer membranes by fine-tuning their morphology. In particular, the understanding of the contribution of the polymer matrix/nanofiller interface to the overall transport properties is key to design membranes with tailored selective and adsorptive properties. In that aim, cellulose nanocrystals (CNC)/polylactide (PLA) nanocomposites were fabricated with chemically designed interfaces, which were ensuring the compatibility between the constituents and impacting the mass transport mechanism. A detailed analysis of the mass transport behaviour of different permeants in CNC/PLA nanocomposites was carried out as a function of their chemical affinity to grafted CNC surfaces. Penetrants (O2 and cyclohexane), which were found to slightly interact with the constituents of the nanocomposites, provided information on the small tortuosity effect of CNC on diffusive mass transport. The mass transport of water (highly interacting with CNC) and anisole (interacting only with designed CNC surfaces) exhibited non-Fickian, Case II behaviour. The water vapour caused significant swelling of the CNC, which created a preferential pathway for mass transport. CNC surface grafting could attenuate this phenomenon and decrease the water transport rate. Anisole, an aromatic organic vapour, became reversibly trapped at the specifically designed CNC/PLA interface, but without any swelling or creation of an accelerated pathway. This caused the decrease of the overall mass transport rate. The latter finding could open a way to the creation of materials with specifically designed barrier properties by designing nanocomposites interfaces with specific interactions towards permeants.